2018
DOI: 10.1542/peds.2018-0820
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana and Tobacco Coexposure in Hospitalized Children

Abstract: BACKGROUND: The impact of secondhand marijuana smoke exposure on children is unknown. New methods allow for the detection of marijuana smoke exposure in children. METHODS: We studied children who were hospitalized in Colorado and had a parent participating in a smoking cessation study; all children had urine samples remaining from the original study as well as consent for future research. Parents completed a survey and urine samples were analyzed for cotinine and marijuana metabolites, including 11-hydroxy-Δ9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, this reported mode of consumption decreased from 64.2% to 52.5% for women who used cannabis. 28 Given the potential risk of second-hand exposure among children from parental cannabis smoking, 29,30 men with children in the home may be less likely to smoke cannabis. Evidence on adverse health outcomes among children exposed to secondhand cannabis smoking and potential risk-modifying behaviours among parents who use cannabis is limited, and additional research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this reported mode of consumption decreased from 64.2% to 52.5% for women who used cannabis. 28 Given the potential risk of second-hand exposure among children from parental cannabis smoking, 29,30 men with children in the home may be less likely to smoke cannabis. Evidence on adverse health outcomes among children exposed to secondhand cannabis smoking and potential risk-modifying behaviours among parents who use cannabis is limited, and additional research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors including tobacco and indoor biomass smoke, outdoor air pollution, and viral infection are particularly common in LMICs 24‐28 and in deprived communities in high‐income countries. Environmental disasters, such as wildfires, hailstorms or floods, also worsen asthma control.…”
Section: Prevalence Of Asthma In Childrenmentioning
confidence: 99%
“…8 While adolescent marijuana use/exposure has been studied, marijuana's impact on younger children has not been fully elucidated. A previous study investigating young children hospitalized with bronchiolitis found almost 50% of children exposed to tobacco also had detectable levels of secondhand marijuana, 9 yet just how marijuana smoke affects children has not been studied in depth. With the rise in marijuana use by adults, the known concerning effects from primary exposure to marijuana, and the similarities of marijuana and tobacco smoke, the examination of secondhand marijuana smoke exposure, and its potential effects on child health is of substantial public health importance.…”
Section: Introductionmentioning
confidence: 99%